A Defense Pathway Linking Plasma Membrane and Chloroplasts and Co-opted by Pathogens - Medina-Puche, Laura; Tan, Huang; Vivek Dogra; Wu, Mengshi; Rosas-Díaz, Tábata Victoria; Liping, Wang; Xue, Ding; Dan, Zhanga; Xing Fu; Chanhong Kim; Lozano-Durán, Rosa (Elsevier, 2020)
Chloroplasts are crucial players in the activation of defensive hormonal responses during plant-pathogen interactions. Here, we show that a plant virus-encoded protein re-localizes from the plasma membrane to chloroplasts upon activation of plant defense, interfering with the chloroplast-dependent anti-viral salicylic acid (SA) biosynthesis. Strikingly, we have found that plant pathogens from different kingdoms seem to have convergently evolved to target chloroplasts and impair SA-dependent defenses following an association with membranes, which relies on the co-existence of two subcellular targeting signals, an N-myristoylation site and a chloroplast transit peptide. This pattern is also present in plant proteins, at least one of which conversely activates SA defenses from the chloroplast. Taken together, our results suggest that a pathway linking plasma membrane to chloroplasts and activating defense exists in plants and that such pathway has been co-opted by plant pathogens during host-pathogen co-evolution to promote virulence through suppression of SA responses.
Keywords: Virus fitopatógenos; SALICYLIC-ACID BIOSYNTHESI; N-MYRISTOYLTRANSFERASE; RESISTANCE; Geminivirus